Geotechnology applied to environmental diagnosis: Biological Reserve of Pinheiro Grosso, Barbacena – Minas Gerais - Brazil - Dias, Natália Oliveira; Martins, Frederico Cássio Moreira; Barros, Kelly de Oliveira (Sociedade & Natureza, 2020)
The Protected Areas (PAs) are territorial spaces that present natural resources with relevant characteristics. Such areas are used as strategy for the environment protection. The use of geotechnologies, such as Geographic Information System and Remote Sensing, optimizes diagnosis and environmental monitoring. The study aimned to analyzed the use and soil occupation as well as the fragility of the current scenario of the Pinheiro Grosso Biological Reserve (ReBio – ReBio, in Portuguese), located in Barbacena - Minas Gerais state - Brazil. Currently, ReBio (ReBio, in Portuguese) areas presents 66.18% occupied by Vegetation and 33.82% by Anthropized area. Multicriteria Analysis revealed that 4.19% of the ReBio (ReBio, in Portuguese) are strongly subject to anthropization. Due to the great anthropic pressure and existing socio-environmental conflicts, its category of Integral Protection does not match its current situation. So, it is suggested the delimitation of unit Damping Zone, the emergency implementation of environmental education programs for the local community, as well as greater supervision and monitoring of the area, as well as its recategorization as a Sustainable Use unit